Pharmacokinetics and efficacy of a novel long-acting bupivacaine formulation for cornual nerve block in calves - Venkatachalam, Dinakaran; Kells, Nikki; Chambers, Paul; Jacob, Antony; Ward, Neil; Singh, Preet (Frontiers in Veterinary Science, 2022)
Local anesthetics are commonly used in farm animals to provide analgesia for painful procedures but can cause adverse effects at high systemic concentrations. The pharmacokinetics and efficacy of a long-acting sucrose acetate isobutyrate (SAIB) bupivacaine formulation following cornual nerve block in calves were compared to lidocaine. Fourteen calves were randomly assigned to one of the treatment groups i) 5% Bupivacaine-SAIB (BUP-SAIB), n=7; or ii) 2% lidocaine (LID), n=7. Cornual nerve block was performed, and duration of effective analgesia was evaluated by nociceptive threshold testing using a hand-held pressure algometer. Blood samples were collected at various time points and plasma concentrations were analyzed by HPLC. Pharmacokinetic parameters were calculated using a non-compartmental model. The mechanical nociceptive thresholds showed that the novel formulation could desensitize the skin around the horn bud for 18.77 ± 8.88 hours (range 8 to 36 hours), compared to 0.79 ± 0.34 hours (range 0.5 to 1.5 hours) with lidocaine. The mean maximum plasma concentration (Cmax) of bupivacaine was 152.03 (SD 37.34) ng/mL and its Tmax was 0.39 (SD 0.13) h. The half-life of elimination was 32.79 ± 11.00 h and the rate of clearance was 0.12 ± 0.03 L h–1. No toxicity signs were seen after treatment in either group. The novel formulation produced long-lasting analgesia of several times greater duration than that produced by lidocaine. This study showed that the safety and efficacy of the SAIB formulation justifies further studies in a larger population of animals.